COMPETITIVE ADVANTAGES STRATEGY ANALYSIS FOR REGIONAL OWNED ENTERPRISES (BUMD): A CASE STUDY FOR PERUMDA KAMPAR ANEKA KARYA - Firli Musfar, Tengku; Noviasari, Henni; Pratiwi, Dian (Penerbit Lafadz Jaya, 2025)
This study aims to analyze internal (strengths, weaknesses) and external (opportunities, threats) factors and formulate competitive advantage strategies for Perumda Kampar Aneka Karya, a Local Government-Owned Enterprise in Kampar District, Riau, Indonesia. Using a qualitative descriptive approach, this research applies strategic management tools, including Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT matrix, and quadrant analysis. Data were collected through in-depth interviews with company leaders, shareholders, and consultants, as well as secondary source exploration. Findings show that Perumda Kampar Aneka Karya has effectively leveraged its strengths and addressed weaknesses. The company also capitalizes on opportunities while mitigating threats. To enhance competitiveness, adopting aggressive strategies is recommended.